ANALISIS KUALITAS TAHU TAKWA DENGAN PENDEKATAN GOOD MANUFACTURING PRACTICES (GMP) DI INDUSTRI RUMAH TANGGA - Desi Listianingsih; R. Azizah (Universitas Airlangga, 2018)
The production process of knowing the traditional poultry requires a supervisory system with Good Manufacturing Practices (GMP) approach as stipulated in Regulation of BPOM Head of 2012 on Good Food Making. The quality of tofu produced by a domestic industry must be in accordance with Indonesian National Standard (SNI) 01-3142-1998 about the quality of tofu so that the products know that piety produced safe. This study aims to analyze the quality of know-how with the approach of Good Manufacturing Practices (GMP) and consumer attitudes toward tofu products in one household industry in Kediri. This research was descriptive with cross sectional approach. Aspects of GMP examined were the location and environment of production, buildings and facilities, production equipment, water supply or water supply facilities, hygiene and sanitation facilities and activities, storage, process control, food labeling, supervision by persons responsible, product recall, record and documentation, and employee training, and see the quality of the IRT. The results of the assessment of the implementation of GMP on IRT know this pardon of 59.67%, included in the category of poor assessment. Therefore, it was necessary to improve the production process from the IRT to know piety against the unfavorable aspects, such as facilities and hygiene and sanitation activities, maintenance and hygiene and sanitation programs, storage, supervision by the responsible person, and recording and documentation, so that aspects it complies with the standards and produces quality tofu according to the standard.